2015
DOI: 10.1111/josh.12346
|View full text |Cite
|
Sign up to set email alerts
|

School Personnel Experiences in Notifying Parents About Their Child's Risk for Suicide: Lessons Learned

Abstract: BACKGROUND Schools across the nation are increasingly implementing suicide prevention programs that involve training school staff and connecting students and their families to appropriate services. However, little is known about how parents are engaged in such efforts. METHODS This qualitative study examined school staff perspectives on parent involvement in the implementation of a district-wide suicide prevention program by analyzing focus group and interview data gathered on the program implementation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Parents will need information on how and where to obtain mental healthcare for their adolescents. They will also need information on the causes of mental health problems and issues regarding the stigma by some toward mental illness [39][40][41]. • Schools need to develop school-community partnerships specifically as ready sources of referral of students who threaten or have attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Parents will need information on how and where to obtain mental healthcare for their adolescents. They will also need information on the causes of mental health problems and issues regarding the stigma by some toward mental illness [39][40][41]. • Schools need to develop school-community partnerships specifically as ready sources of referral of students who threaten or have attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the studies with qualitative elements (D'Souza et al 2005;Kirk 2014;Nadeem et al 2016;Whitney et al 2011) scored well on the CASP tool, indicating appropriate research design, recruitment, data collection, and data analysis. Each study also included a clear statement of aims and findings and added value to the evidence base.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Eight studies reported on the feasibility of staff in-service training, six of which focused on identification of suicide risk (Eckert et al 2003;Eckert et al 2006;Kalafat and Elias 1994;Miller et al 1999;Nadeem et al 2016;Scherff et al 2005;Whitney et al 2011) and one of which on ADHD (Sayal et al 2006). All but two studies (Nadeem et al 2016;Sayal et al 2006) examined in-principle feasibility and all examined the views of school staff.…”
Section: Staff In-service Trainingmentioning
confidence: 99%
See 2 more Smart Citations